Actividades lúdicas y su influencia en el aprendizaje significativo de estudiantes del 2do año de EGB de la U.E. Abdón Calderón Muñoz, periodo 2023 - Vega Mendez, Yadira Mariuxi (2023)
Playful activities are strategies that have a significant relevance in learning and their absence is notable in the poor academic performance of students where play helps develop innate abilities and skills of the human being, which is why it is necessary for teachers to establish spaces and time within the class aimed especially at the development of recreational activities. Children get bored of doing the same thing every day and even adults find the monotony suffocating. The biggest advantage of the game is learning by playing. Playful activities represent all of their innate learning in children under 6 years of age, but recently play was considered a learning method in which children could communicate without fear, expressed themselves fluently, and contributed increasingly to resolution. to some problem therefore the present research work called Playful activities and their influence on the significant learning of students of the 2nd year of EGB of the U.E. Abdón Calderón Muñoz, period 2023, has the general objective of determining the influence of recreational activities on the significant learning of students in the 2nd year of EGB of the U.E. Abdón Calderón Muñoz, period 2023. Due to the context of his research, it was based on a qualitative approach, where the bibliographic technique was used and through a very in-depth search, the information was obtained to develop the dimensions of the two variables that make up the topic of this case study. In addition, the interview was applied as a research instrument with two teachers from the 2nd year of EGB as a sample to collect relevant information based on the objectives and an observation sheet was also applied to the children from the 2nd year of EGB with indicators on the influence of recreational activities on meaningful learning.